"Antiscience Zealotry"? Values, Epistemic Risk, and the GMO Debate. Issue 3 (July 2018) - Biddle, Justin B.
Abstract : This article argues that the controversy over genetically modified crops is best understood not in terms of the supposed bias, dishonesty, irrationality, or ignorance on the part of proponents or critics, but rather in terms of differences in values. To do this, the article draws on and extends recent work of the role of values and interests in science, focusing particularly on inductive risk and epistemic risk, and it shows how the GMO debate can help to further our understanding of the various epistemic risks that are present in science and how these risks might be managed.